Uji Aktivitas Antibakteri Ekstrak Etil Asetat Jamur Gliocladium sp T.N.C73 dengan Kromatografi Lapis Tipis-Bioautografi - Emma - Susanti; Rahayu Utami; Raja Adli Husein; Titania T Nugroho (LPPM Universitas Abdurrab, 2026)
Gliocladium sp. is a fungus that functions as a biological control agent against plant pathogens. Research on the activity of Gliocladium sp. not yet against human pathogens. The aim of this study was to determine the antibacterial profile of ethyl acetate extracts of Gliocladium sp. T.N.C73 (LBKURCC3) using the TLC-bioautography method against E. coli ATCC 25922 and S. aureus ATCC 25923. The test results showed that the ethyl acetate extract of the fungus Gliocladium sp. exhibited antibacterial activity against S. aureus dan tidak menghambat E. coli whereas against, it showed antibacterial activity characterised by the formation of a clear area and verified with resazurin (blackish blue colour). Resazurin is used as a redox indicator in bacterial cell viability and proliferation tests. The conclusion of this study is that the ethyl acetate extract of Gliocladium sp. T.N.C73 (LBKURCC3) fungus can inhibit S. aureus bacteria.